2020
DOI: 10.1136/neurintsurg-2020-016502
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendovascular clinical trials disruptions due to COVID-19. Potential future challenges and opportunities

Abstract: To assess the impact of COVID-19 on neurovascular research and deal with the challenges imposed by the pandemic.MethodsA survey-based study focused on randomized controlled trials (RCTs) and single-arm studies for acute ischemic stroke and cerebral aneurysms was developed by a group of senior neurointerventionalists and sent to sites identified through the clinical trials website ( Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 19 publications
(18 reference statements)
3
9
0
Order By: Relevance
“…A survey study of neurointerventional research centers revealed widespread disruptions in aneurysm and stroke clinical trials due to missed enrollments and protocol deviations from missed clinical or imaging follow-up. 15 Similar reductions in oncologic clinical trial enrollment have been reported. 16 Given the dramatic increase in submissions for 2020 in the setting of widespread disruptions in ongoing prospective studies, one could argue that the quality of submissions may have decreased during the pandemic lockdown period.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…A survey study of neurointerventional research centers revealed widespread disruptions in aneurysm and stroke clinical trials due to missed enrollments and protocol deviations from missed clinical or imaging follow-up. 15 Similar reductions in oncologic clinical trial enrollment have been reported. 16 Given the dramatic increase in submissions for 2020 in the setting of widespread disruptions in ongoing prospective studies, one could argue that the quality of submissions may have decreased during the pandemic lockdown period.…”
Section: Discussionsupporting
confidence: 59%
“…A survey study of neurointerventional research centers revealed widespread disruptions in aneurysm and stroke clinical trials due to missed enrollments and protocol deviations from missed clinical or imaging follow-up. 15 Similar reductions in oncologic clinical trial enrollment have been reported. 16 …”
Section: Discussionsupporting
confidence: 59%
“…Furthermore, its use may be extended to research settings, given the widespread disruption of research during the pandemic. 9 The limitations of virtual care are largely related to the inability to physically examine a patient. However, many aspects of the neurological examination can be adapted to be virtually assessed, particularly if screen-sharing is available through the video conference platform.…”
Section: Discussionmentioning
confidence: 99%
“…Surveys designed to address highpriority issues in other medical specialties have unanimously demonstrated marked disruptions in clinical practice. [27][28][29][30] Although the present study did not specifically address the effects of COVID-19 on neurovascular research, a concomitant study has also revealed widespread disruptions in aneurysm and stroke clinical trials due to missed enrollments and protocol deviations from missed clinical or imaging follow-up 31 These broad vantage points are particularly important given the widespread fears about resurgent infection, 32 33 with the persistence of the virus in communities across the US. This data helps inform current responses, but also future ones in the event of subsequent pandemics.…”
Section: Discussionmentioning
confidence: 99%